2018
DOI: 10.3390/jcm7120537
|View full text |Cite
|
Sign up to set email alerts
|

Global Expression Profiling Identifies a Novel Hyaluronan Synthases 2 Gene in the Pathogenesis of Lower Extremity Varicose Veins

Abstract: Lower extremities varicose veins (VV) are among the most easily recognized venous abnormalities. The genetic mechanism of VV is largely unknown. In this study, we sought to explore the global expressional change of VV and identify novel genes that might play a role in VV. We used next-generation ribonucleic acid (RNA) sequence (RNA seq) technology to study the global messenger RNA expressional change in the venous samples of five diseased and five control patients. We identified several differentially expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
4
1
Order By: Relevance
“…Some studies indicated altered expression of genes in veins obtained from patients with CVD and venous ulcers [57][58][59][60] but none of the genes indicated in abovementioned research were found in our study. These differences could be related to the biological material type, inclusion criteria and methodological approach.…”
Section: Discussioncontrasting
confidence: 73%
“…Some studies indicated altered expression of genes in veins obtained from patients with CVD and venous ulcers [57][58][59][60] but none of the genes indicated in abovementioned research were found in our study. These differences could be related to the biological material type, inclusion criteria and methodological approach.…”
Section: Discussioncontrasting
confidence: 73%
“…For Part I of this study, we compared the comorbidities and demographic characteristics of the study and comparison cohorts; here, we used Pearson’s chi-square test and an unpaired Student t test to compare categorical and continuous variables, respectively 31 . Next, we included control variables such as sex, age, income level, urbanization level, and comorbidities as covariates in our univariate model to perform a univariate analysis 32 . The variables with p < 0.1 in the univariate analysis were included in the multivariate analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, some of the cardiac defects can be rescued in explants from Has2 À/À mice by exogenous HA [65,66]. Interestingly, knockdown of Has2 in zebrafish leads to abnormal blood vessels with static venous flow, suggesting that HAS2 might be involved in the pathogenesis of venous disease as well [67].…”
Section: Role Of Hyaluronan Synthases In Malignancymentioning
confidence: 99%